PHYSICAL CHARACTERISTICS AND DISASTER RISK PERCEPTION CORRELATION AT BANTUL REGENCY - Suryanto; Mudrajat Kuncoro; Junun Sartohadi (Universitas Islam Indonesia, 2012)
This paper analyses the correlation between vulnerable areas and resident's risk perception. For such purpose, it uses descriptive and correlation analysis. The mapping of the vulnerable area is based on the vulnerability levels, which were analyzed with the Geographical Information System (GIS). The GIS and correlation analysis show that education level and income rate of the respondents have negative correlations with level of vulnerability in the area. The perception index has a positive correlation with level of vulnerable in the area. These results are different from the degree of the risk averse variable that does not significantly correlate with the level of hazardous area. Keywords: earthquake risk perception, economic valuation, GISJEL Classification Numbers: Q54, R29AbstrakMakalah ini menganalisis korelasi antara daerah yang rentan bencana dan persepsi mereka terhadap risiko.Penelitian ini menggunakan metode analisis deskriptif dan korelasi. Pemetaan daerah rawan didasarkan pada tingkat kerentanan, yang dianalisis dengan Sistem Informasi Geografis (SIG). Hasil analisis menunjukkan bahwa tingkat pendidikan dan tingkat pendapatan responden memiliki korelasi negatif dengan tingkat kerentanan di daerah. Indeks Persepsi memiliki korelasi positif dengan tingkat kerentanan suatu daerah. Hasil ini berbeda dengan tingkat risiko variabel yang tidak signifikan berkorelasi dengan tingkat daerah bahaya.Keywords: Persepsi risiko gempa bumi, penilaian ekonomi, SIGJEL Classification Numbers: Q54, R29